Pengaruh Audit Investigasi Terhadap Pencegahan Dan Pengungkapan Fraud - Anggi Sari Tambunan; Alisa Afrianti; Khairatul Muna (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study discusses the importance of investigative audits in uncovering fraud and corruption in Indonesia. Investigative audits are conducted using specific approaches, procedures, and techniques that are different from regular audits. The auditor's investigative ability is indispensable in identifying fraud. Fraud prevention is also important to eliminate the causes of fraud. The professionalism of auditors also plays an important role in fraud disclosure. The research method used in this study is qualitative by conducting a literature review to support the findings. Investigative audits are described as audits that aim to identify and uncover fraud, by involving fraud prevention strategies in financial statements. Forensic audits and investigative audits are proposed as solutions to prevent fraud. In the context of repressive actions, investigative audits are considered as steps to deal with fraud that occurs. To increase the role of investigative audit in uncovering fraud, it is necessary to improve the skills and experience of investigative auditors, adequate resource allocation, and establish good cooperation with related parties